Risk factors associated with pregnancy outcomes in patients with recurrent pregnancy loss after treatment - Tingfeng Fang; Xiaohui Ji; Ziyang Su; Ao Zhang; Liqiong Zhu; Jing Tang; Zhuoyao Mai; Haiyan Lin; Nengyong Ouyang; Hui Chen (BMC Pregnancy and Childbirth)
Abstract Background The treatment for recurrent pregnancy loss (RPL) has been addressed in international guidelines. However, limited studies have investigated the risk factors associated with pregnancy and live birth outcomes in patients with RPL after treatment. The objective of this study was to offer a comprehensive assessment of the risk factors for pregnancy loss in patients with a history of RPL following therapeutic interventions. Methods This retrospective cohort study involved 431 women in early pregnancy with a history of RPL who experienced treatment at the Department of Obstetrics and Gynecology, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, between June 2018 and June 2020. The main outcome measures were the ongoing pregnancy ≥ 12 weeks and the live birth outcomes. Univariate and multivariate logistic regression analyses were conducted to identify the risk factors for pregnancy loss < 12 weeks and live birth outcomes. Results Patient’s age and the prevalence of uterine malformations were significantly different between the patients with and without ongoing pregnancy ≥ 12 weeks (32.64 ± 5.08 vs. 31.54 ± 4.34, P = 0.026; 34.70% vs. 24.60%, P = 0.035). The risk of pregnancy loss < 12 weeks was significantly increased with age and those with uterine abnormalities (adjusted OR: 1.48 [95% CI: 1.05 to 2.07], P = 0.025; adjusted OR:1.78 [95% CI 1.11 to 2.79], P = 0.016). The risk of non-live birth was significantly increased in couples with parental karyotype abnormalities (adjusted OR: 0.08 [95% CI 0.01 to 0.76], P = 0.029). No statistically significant differences were found between the patients with and without ongoing pregnancy ≥ 12 weeks and live birth regarding number of miscarriages, BMI, thyroid stimulating hormone, thyroid peroxidase antibody, thyroglobulin antibody, homa insulin-resistance, parental karyotype abnormality, B lymphocyte, NK cells, antinuclear antibody, antithrombin III activity, platelet aggregation function, anticardiolipin antibody, lupus anticoagulant, homocysteine, protein C, protein S, anti-β2 glycoprotein antibody, anti-phosphatidylserine and thromboelastograms. Conclusions In patients with RPL after treatment, age and uterine anomalies were identified as risk factors linked to pregnancy loss < 12 weeks, while parental karyotype abnormalities were recognized as an independent risk factor affecting live birth outcomes. Clinical trial number Not applicable.